An emotion recognition system: bridging the gap between humans-machines interaction - Ahmed Nouman; Hashim Iqbal; Muhammad Khurram Saleem (IAES International Journal of Robotics and Automation (IJRA), 2023)
Human emotion recognition has emerged as a vital research area in recent years due to its widespread applications in psychology, healthcare, education, entertainment, and human-robot interaction. This research article comprehensively analyzes a machine learning-based six-emotion classification algorithm, focusing on its development, evaluation, and potential applications. The study aims to assess the algorithm's performance, identify its limitations, and discuss the importance of selecting appropriate image descriptors for accurate emotion classification. The algorithm achieved an overall accuracy of 92.23%, showcasing its potential in various fields. However, the classification of specific emotions, particularly "excited" and "afraid", demonstrated some limitations, suggesting further refinement. The study also highlights the significance of choosing suitable image descriptors, with the manual distance calculation used in the framework proving effective. This article offers insights into developing and evaluating a six-emotion classification algorithm using a machine learning framework, emphasizing its strengths, limitations, and possible applications in multiple domains. The findings contribute to ongoing efforts in creating robust, accurate, and versatile emotion recognition systems that cater to the diverse needs of various applications across psychology, healthcare, robotics, education, and entertainment.